The Impact of Domestic Gastronomic Festivals on the Local Accomodations - István Bottyán (DETUROPE)
Food festivals are a mainstay of the festival sector and some surveys show that they currently account for 30 percent. Despite this, we know very little about this important part of event tourism, and its economic and social impacts. This study tries to show, by econometric methods, the impacts on the local economy made by food festivals – and, at the same time, fhe effects -of the multiplicator and spillover factors. This paper looks for some correlation between the local index-number of tourism and gastronomic festivals, using data from more than 200 events and festivals and 123 settlements. The first step in the survey was to determine two tourism factors, and this was followed by our methodological studies of these factors. Although the summarized conclusions may not support the general opinion as can be found in the relevant literature – that is, a positive correlation between gastronomic festivals and local tourism, new research directions are revealed.